Evaluation of Moslems\' Fasting Effects on Myopia (Short Sighted Vision) - Mahmoud Farmad (University of Social Welfare and Rehabilitation Sciences, 2003)
Objective: Considering daily fasting in the holy month of Ramadan, there are some speculations and gossips, which make people believe negative effects of fasting on refractive errors exist actually. Materials & Methods: This investigation was carried out on 180 eyes (90 patients) in two age groups: 12 to 19 year old and 20 to 30 year old individuals, which all have some degree of myopia and were selected randomly due to their attendance in a general ophthalmology clinic. The examinations were performed in 2 stages. Firstly, 3 days prior to Ramadan up to the eve of it and secondly, from the next day of Eid ul-Fitr lasting to 3 days later. Results: Using same examiner, examination set and E. Chart in this study, not a specific outcome was drawn of statistical results in these two groups and one can say the fasting has not obvious consequences on myopia in practice.